Rehabilitation and reintegration of Fistula Clients through Micro credit linked services - Mohiddin, Sheikh; Haque, Fazlul; Huda, Sk Nazmul (Nepal Journal of Obstetrics and Gynaecology, 2018)
Objectives: To describe the process and performance of reintegration and rehabilitation of women with Fistula through microcredit linked services in north-western region in Bangladesh.Introduction: Ad-din Social Financing for Community Health Development is a non profit microcredit system established in 1996. The program provides small capital and technical assistance for entrepreneurship development for its members, particularly women from underprivileged communities.Methods: 56 paramedics linked with Ad-din microcredit system were provided training on fistula case identification, referral, reintegration and rehabilitation. The paramedics identified fistula clients and conducted customized need assessments for their reintegration and rehabilitation services. This included liveihood skills training, financial assistance for fistula clients or their family members and mobilization of local institutions.Results: Out of 86 fistula clients identified by paramedics, 76 were in need of rehabilitation services and 12 were in need of reintegration support. Only three (4%) were covered by government safety net services. The program provided customized skill training to 43 fistula clients or family members. Three fistula clients were selected for food box drop at their place of residence.  Conclusions: Customized need assessment of reintegration and rehabilitation of fistula clients is effective for sustainable result. The field resources of a micro credit system, which is present in many settings with a fistula burden, can efficiently provide rehabilitation services to fistula clients.